Concurrent Morgagni and Bochdalek congenital diaphragmatic hernias with omphalocele - Insiyah Campwala; Bryanna Emr; Ayesha M. Sulaiman; Abeer A. Azzuqa; Burhan Mahmood; Kelly Austin (Elsevier, 2021)
Congenital diaphragmatic hernia (CDH) is a well-documented developmental abnormality in the formation of the diaphragm, resulting in herniation of bowel into the thorax causing pulmonary hypoplasia. CDH has been associated with many genetic syndromes and other anatomic anomalies including craniofacial, cardiac, skeletal, brain, ocular, renal, and abdominal wall defects. Despite this, co-occurrence of CDH and omphalocele is rare and only identified within 0.63% of neonates with CDH. Most congenital diaphragmatic hernias are located posterolateral (Bochdalek hernias) or anterior retrosternal or parasternal (Morgagni hernias); bilateral diaphragmatic hernias are rare. We describe the first documented case of concurrent Bochdalek and Morgagni hernias with an omphalocele and no other associated anatomic anomalies.